Enhancing Ornamental Fish Health and Aquaculture Sustainability: A Review on the Role of Probiotics in Disease Resistance, Gut Health, and Growth Performance - R. C. Ramya,; A. Palavesam, (The Bioscan, 2025)
Ornamental fish farming, a burgeoning industry, faces challenges related to fish health, disease management, and environmental impacts. This review explores the potential of probiotics, particularly strains of Lactobacillus and Bacillus, to address these challenges by enhancing fish health, growth performance, and disease resistance. Probiotics offer an environmentally sustainable alternative to traditional antibiotics, facilitating improved nutrient absorption, optimizing gut health, and reducing pathogenic infections. Despite their benefits, variability in effectiveness across fish species and environmental conditions suggests the need for tailored probiotic formulations. This review emphasizes the mechanisms through which probiotics improve aquaculture outcomes, including enzymatic activity, immune modulation, and competitive exclusion. Additionally, the paper discusses the challenges and future directions for optimizing probiotic use in aquaculture, aiming to promote sustainability while minimizing ecological impact. These insights support the integration of probiotics as a viable strategy for advancing ornamental fish farming and achieving more sustainable aquaculture practices.